MEDIA LITERASI ALTERNATIF: STUDI KASUS PADA TEENLIT DI POSTINGAN INSTAGRAM AKUN “SASTRAARABCOM” - Hendro Eko Setiawan (SASDAYA: Gadjah Mada Journal of Humanities, 2020)
The purpose of this research is to find teenlit in the Instagram account of Sastraarabcom which can be used as a medium to improve literacy culture among adolescents. to improve the literature faced by adolescents, writers must use various approaches, such as writing things they like, discussions, simulations, questions and answers and the like. Such a contextual approach is a key element in increasing adolescent learning interest. The results showed that teenlit Sastraarabcom can improve and become an alternative media in increasing teenage literacy, not only being able to read but can understand the contents of reading, with the hope of moral messages such as peace, social care, social values, mutual cooperation, values moral, and mutual respect between friends will be reflected in the actions of future adolescent behavior.